ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ҚОБЛАН»: ЖЫЙНАЛЫЎ, БАСЫП ШЫҒАРЫЛЫЎ ҲӘМ ИЗЕРТЛЕНИЎ ТАРИЙХЫНАН - Палымбетов, К.С. (SCIENCE and SOCIETY, 2019)
The article deals with the research, gathering and printing of the songs in the epos “Koblan”. The author gives information about the history of investigation of this issue, and analyses the conclusions and opinions of scholars in their scientific works on the history of the issue.